The Impact of Inclusive STEM High Schools on Student Achievement - Jennifer Gnagey; Stéphane Lavertu (SAGE Publishing, 2016)
This study is one of the first to estimate the impact of "inclusive" science, technology, engineering, and mathematics (STEM) high schools using student-level data. We use multiple statistical strategies to estimate the effect on student achievement from 2 years of attendance at six such high schools in Ohio. The results indicate that two schools had positive effects on science achievement that appear to come at the expense of achievement in social studies. The other schools had negligible or, often, negative effects across both STEM and, particularly, non-STEM subjects. These results are consistent with studies indicating that inclusive STEM schools typically focus on problem-based, personalized learning rather than science and mathematics content. The analysis also reveals the importance of accounting for students' prior test scores in science, in addition to math and reading, when estimating models that use only 1 year of prior test score data-something that existing studies fail to do.